Village Among Nations : "Canadian" Mennonites in a Transnational World, 1916-2006 - Loewen, Royden, 1954- (Book collections on Project MUSE., 2013)
Village among Nations recuperates a missing chapter of Canadian history: the story of traditionalist Mennonites who emigrated from Canada for cultural reasons, but then in later generations "returned" in large numbers for economic and social security.